2007
DOI: 10.1039/b617347k
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i)–isocyanide and gold(i)–carbene complexes as substrates for the laser decoration of gold onto ceramic surfaces

Abstract: Gold-isocyanide complexes XAu(RNC) (X = halide, pseudohalide, R = alkyl, aryl) and water soluble gold-carbene complexes XAuC(NHPh)[MeN(CH(2)CH(2)O)(n)Me] (X = Cl, n = 1-11) have been prepared and evaluated as substrates for the direct laser writing of gold decoration onto ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Signal multiplicity is given as follows: s (singlet), d (doublet), t (triplet), q (quartet), m (multiplet). 13 C NMR assignments were achieved via HSQC and DEPT135 spectra. Mass spectra were recorded on Finnigan MAT TSQ 700, Vacuum Generators ZAB-2F and JEOL JMS-700 spectrometers.…”
Section: Experimental Section General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal multiplicity is given as follows: s (singlet), d (doublet), t (triplet), q (quartet), m (multiplet). 13 C NMR assignments were achieved via HSQC and DEPT135 spectra. Mass spectra were recorded on Finnigan MAT TSQ 700, Vacuum Generators ZAB-2F and JEOL JMS-700 spectrometers.…”
Section: Experimental Section General Methodsmentioning
confidence: 99%
“…Two years later the same authors also reported the synthesis of the first five nitrogen acyclic carbene (NAC, Figure 2) complexes of gold by addition of primary amines to isonitrilegold chloro complexes. [11] Applications of the isonitrile and NAC gold complexes in the field of luminiscent compounds, [12] laser-induced writing with gold on ceramic surfaces, [13] liquid crystals [14] and water-soluble complexes [14] have been reported. The first NHC complex of gold(I) was prepared in 1989, [15] and at present these gold carbene complexes are the dominating car- …”
Section: Introductionmentioning
confidence: 99%
“…All analytical data are in good agreement with the previously reported values. [29] Synthesis of cis-[PtCl 2 (2,6- …”
Section: Synthesis [Aucl(tert-butyl Isonitrile)] (8)mentioning
confidence: 99%
“…As an alternative to thermally induced decomposition, the use of a YAG laser beam focused on the complexes also leads to metal deposition as recently reported by some of us and others. [29,30] The development and optimisation of better metal deposition conditions are in progress.…”
Section: Palladium Complexesmentioning
confidence: 99%